Titration of medications and outcomes in multi‐ethnic heart failure cohorts (with reduced ejection fraction) from Singapore and New Zealand. (1st February 2023) - Teng, Tiew‐Hwa Katherine; Tay, Wan Ting; Ouwerkerk, Wouter; Tromp, Jasper; Richards, A. Mark; Gamble, Greg; Greene, Stephen J.; Yiu, Kai‐Hang; Poppe, Katrina; Ling, Lieng Hsi; Lund, Mayanna; Sim, David; et al.
Abstract: Aims: We investigated titration patterns of angiotensin‐converting enzyme inhibitors (ACEis)/angiotensin receptor blockers (ARBs) and beta‐blockers, quality of life (QoL) over 6 months, and associated 1 year outcome [all‐cause mortality/heart failure (HF) hospitalization] in a real‐world population with HF with reduced ejection fraction (HFrEF). Methods and results: Participants with HFrEF (left ventricular ejection fraction <40%) from a prospective multi‐centre study were examined for use and dose [relative to guideline‐recommended maintenance dose (GRD)] of ACEis/ARBs and beta‐blockers at baseline and 6 months. 'Stay low' was defined as <50% GRD at both time points, 'stay high' as ≥50% GRD, and 'up‐titrate' and 'down‐titrate' as dose trajectories. Among 1110 patients (mean age 63 ± 13 years, 16% women, 26% New York Heart Association Class III/IV), 714 (64%) were multi‐ethnic Asians from Singapore and 396 were from New Zealand (mainly European ethnicity). Baseline use of either ACEis/ARBs or beta‐blockers was high (87%). Loop diuretic was prescribed in >80% of patients, mineralocorticoid receptor antagonist in about half of patients, and statins in >90% of patients. At baseline, only 11% and 9% received 100% GRD for each drug class, respectively, with about half (47%) achieving ≥50% GRD for ACEis/ARBs or beta‐blockers. At 6 months, a large majority remained in the 'stay low' category, one third remained in 'stay high', whereas 10–16% up‐titrated and 4–6% down‐titrated. Patients with lower (vs. higher) N‐terminal pro‐beta‐type natriuretic peptide levels were more likely to be up‐titrated or be in 'stay high' for ACEis/ARBs and beta‐blockers ( P = 0.002). Ischaemic aetiology, prior HF hospitalization, and enrolment in Singapore (vs. New Zealand) were independently associated with higher odds of 'staying low' (all P < 0.005) for prescribed doses of ACEis/ARBs and beta‐blockers. Adjusted for inverse probability weighting, ≥100% GRD for ACEis/ARBs [hazard ratio (HR) = 0.42; 95% confidence interval (CI) 0.24–0.73] and ≥50% GRD for beta‐blockers (HR = 0.58; 95% CI 0.37–0.90) (vs. Nil) were associated with lower hazards for 1 year composite outcome. Country of enrolment did not modify the associations of dose categories with 1 year composite outcome. Higher medication doses were associated with greater improvements in QoL. Conclusions: Although HF medication use at baseline was high, most patients did not have these medications up‐titrated over 6 months. Multiple clinical factors were associated with changes in medication dosages. Further research is urgently needed to investigate the causes of lack of up‐titration of HF therapy (and its frequency), which could inform strategies for timely up‐titration of HF therapy based on clinical and biochemical parameters.